Antonio Gramsci i pedagogika krytyczna. Hegemonia, edukacja i zadania intelektualistów - Kruszelnicki, Wojciech (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2016)
This paper illuminates the intellectual inspirations that critical pedagogy, particularly in its form envisaged by Henry A. Giroux, has drawn from the work of Italian Marxist thinker – Antonio Gramsci. Herein I offer a reading of Gramsci’s seminal book of essays, „The Prison Notebooks”, and pinpoint its pedagogical relevance. I argue that it was Gramsci’s influence that prompted Giroux to develop the conception of “teachers as public intellectuals” and to examine such essential critical issues in education as culture and ideology, popular culture, subjectivity, student voice, and teachers’ leading role in a struggle for a reinvigorated public sphere and democratic society.
Keywords: education; Gramsci, Antonio (1891-1937); marxism; critical pedagogy; hegemony; ideology; emancipation